Preparation and characterization of Zinc(II) and Nickel(II) Phenylethanoldithiocarbamate / Norain Isa, Nurul Izza Husin, Nor Aimi Abdul Wahab and Ibrahim Baba - Abdul Wahab, Nor Aimi; Baba, Ibrahim; Isa, Norain; Husin, Nurul Izza (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2012)
Dithiocarbamate compounds have been found to be biologically active. A new series of Zinc(II) and nickel(II) phenylethanoldithiocarbamate [Zn(Phe-EtoH-Dtc)2 and Ni(Phe-EtoH-Dtc)2] complexes were synthesized from 2-(hydroxyethyl)aniline, carbon disulfide and metal salts by using the in-situ method. The resulting new complexes have been characterized by CHNS-O analysis, melting point, gravimetric analysis as well as FTIR spectral study. The presence of ν(CN) and ν(CS) band in the infrared spectra confirmed the presence of dithiocarbamate ligand in the compound.